Caricature in the Newspaper „Tēvija“ (1941–1945). Some Questions of Source Criticism - Zellis, Kaspars; Olechnovič, Dmitrij (Genocidas ir rezistencija, 2005)
Current Latvian historical research is characterised by a relaxed approach to the study of historical sources. One of the least researched issues in the Latvian historical sources is cartoons, which were printed in periodicals at various times. This gap can be partly filled by studying cartoons published in periodicals that were released in Latvia during the German occupation.